Effects of digitalized university curriculum-associated teaching on the equilibrium of autonomic neurophysiology and disposition of learners in medical school (EDUCATE-AND-LEARN): protocol for a randomized crossover study. (1st January 2021) - Woranush, Warunya; Sedghi, Annahita; Moskopp, Mats Leif; Japtok, Julia; Ziegler, Christian G.; Barlinn, Jessica; Mirow, Lutz; Noll, Thomas; Siepmann, Timo
Abstract: Background: Homoeostasis of the autonomic nervous system (ANS) contributes to cognitive functional integrity in learners and can be greatly influenced by emotions and stress. While moderate stress can enhance learning and memory processes, long-term stress compromises learning performance in a face-to-face classroom environment. Integrative online learning and communication tools were shown to be beneficial for visualization and comprehension but their effects on the ANS are poorly understood. We aim to assess the effects of video conference-supported live lectures compared to on-site classroom teaching on autonomic functions and their association with learning performance. Methods and Design: Fifty mentally and physically healthy medical students will be enrolled in a randomized two-period crossover study. Subjects will attend a seminar, which is held in face-to-face and simultaneously transmitted via videoconference. Subjects will be allocated in two arms in a randomized sequence determining the order in which both seminar settings will be attended. At baseline and throughout the interactive seminar subjects will undergo detailed autonomic testing comprising neurocardiac (heart rate variability), sudomotor (sympathetic skin response), neurovascular (laser Doppler flowmetry) and pupillomotor (pupillography) function. Furthermore, learning progress will be evaluated using pre- and post-tests on the seminar subject and emotions will be assessed using profile of mood state (POMS) questionnaire. Statistical Analysis: Carryover effects will be handled using a two-way repeated measures (mixed model). Between-group differences (baseline vs face-to-face vs videoconference) will be determined using one-way analysis of variance ANOVA followed by Student–Newman–Keul test. Limitations and Strengths: This study may elucidate complex interactions between autonomic and emotional dynamics during conventional on-site and video conference-based teaching, thus providing a basis for customized learning and teaching methods. Understanding and utilizing advanced distance learning strategies is particularly important during the current pandemic, which has been limiting on-site teaching dramatically in nearly all countries of the world.